2020
DOI: 10.30534/ijatcse/2020/15952020
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Models for the Prediction the Necessity of Resorting to ICU of COVID-19 Patients

Abstract: The world is currently facing many unrests and challenges due to the emergence of the COVID-19 Epidemic. The management of medical resources is considered one of the most important challenges posed by the emergence of this epidemic. The intensive care unit (ICU) plays an important role in saving the life of a COVID-19 patient, and therefore work has been done in this research to find models to predict the patient's need to enter ICU or not. The prediction models depend on Machine Learning (ML). Three models wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…In addition, the critical patients at admission time were discarded from the analysis. Thus, if validated, these features could be applied for predicting the Many studies have focused on determining the key risk factors for ICU admission (8,9,11,13,24,25). The ten top clinical variables predicting ICU risk in reviewed studies encompassed age (older age), body temperature (high), oxygen saturation (decreased), neutrophil count and lymphocyte count (raised), C-reactive protein (elevated), D-dimer (increased), ALT and/or AST (augmented), LDH (elevated), loss of consciousness, and hypertension/cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the critical patients at admission time were discarded from the analysis. Thus, if validated, these features could be applied for predicting the Many studies have focused on determining the key risk factors for ICU admission (8,9,11,13,24,25). The ten top clinical variables predicting ICU risk in reviewed studies encompassed age (older age), body temperature (high), oxygen saturation (decreased), neutrophil count and lymphocyte count (raised), C-reactive protein (elevated), D-dimer (increased), ALT and/or AST (augmented), LDH (elevated), loss of consciousness, and hypertension/cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Ac-cordingly, predicting the individual disease courses and outcomes is essential for triaging patients, customized care service provision, utilizing life-saving resources in the best possible way, and directing them toward vulnerable and at-risk sub-groups deteriorating to critical COVID-19. Furthermore, many problems resulting from the shortage of hospital resources can be overcome by predicting the risk of patient deterioration, determining the length of stay, using hospital resources efficiently, and managing bed turnover (9,10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To have the most relevant classifier and an effective and efficient model, the researchers utilized the Naï ve Bayes Classification Algorithm, a simple technique for constructing classifiers or models based on Bayes Theorem of conditional probability and strong independence assumptions. Many researchers have previously used it and observed that among other classification approaches, Naï ve Bayes performs well [2,3,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%